The Voice-Over of Administration: Reading Ottoman Archives at the Risk of Ill-literacy - Marc Aymes (European Journal of Turkish Studies)
Although the Ottoman state has deservedly been considered a world of paper in itself, and an overflowing one at that, its protagonists also had reasons not to rely on written documents. Drawing on archives from the 19th-century Ottoman administration, and focusing on the province of Cyprus, the present article unearths the oral and aural authority on which imperial rule rested. It shows that this authority was embedded, thanks to a semantic interplay of cultural and religious references, in the language of administration. It proceeds through a semantic review of the various turns of phrase that Ottoman officials and provincial ‘notables’ employed in the business of provincial rule, arguing that their administrative taxonomies could be challenged, unraveled or stained by the rogue words of their ‘common’ interlocutors. Scholarly readings of the Ottoman archives hence need to acknowledge the oral character of these lettered pieces, and to account for the dissension of unpalatable utterances troubling their graphic order.